Nitobe Inazō and the Sapporo Band: Reflections on the Dawn of Protestant Christianity in Early Meiji Japan - Oshiro, George M. (Japanese journal of religious studies, 2007)
This paper focuses on the famous prewar internationalist Nitobe Inazō, and inquires into the origins of his Christian faith. Born in 1862 in Morioka in the last years of the Tokugawa period, he imbibed Christianity while attending the Sapporo Agricultural College. That institution's unique historical environment, and the spiritual legacy implanted there by its charismatic founding president, William S. Clark, is described, and it is demonstrated how Inazō and his classmates were profoundly influenced by New England puritan values in their early exposure to Protestant Christianity. It follows Inazō on his six-and-a-half years of study abroad, and traces his inward struggles to attain a genuine Christian faith free from the taint of foreign culture. His academic studies in the United States and Germany is described in detail. Special attention is paid to his Quaker religious experiences, since these left indelible marks upon his later life and career. Peculiar tenets of his faith and mentioned, and one in particular-the doctrine of pacifism-is highlighted; one which many people who have studied Nitobe's career feel he failed to resolve adequately. Finally, there are some remarks about the legacy of the Sapporo Band, of whom Satō Shōsuke, Ōshima Masatake, Uchimura Kanzō, Miyabe Kingo, and Nitobe stand out most notably today.